Liver Transcriptomic Reveals Novel Pathways of Empagliflozin Associated With Type 2 Diabetic Rats - Lv, Qiuyue; Le, Liang; Xiang, Jiamei; Jiang, Baoping; Chen, Sibao; Xiao, Peigen (Frontiers in Endocrinology, 2020)
The hypoglycaemic target of empagliflozin (EMP), as a novel inhibitor of sodium-glucose cotransporter (SGLT2), is clear. However, recent studies have shown that EMP also has an important role in lipid metabolism and cardiovascular diseases. The liver plays an important role in the development of type 2 diabetes (T2D), although whether EMP affects liver glucose metabolism is currently not reported. This study was designed to evaluate the effect of EMP on hepatic glucose metabolism in T2D and the underlying mechanism. A model of T2D was established by a high-fat and glucose diet (HFD) combined with streptozotocin (30 mg/kg) in male Wistar rats. Serum samples were collected to measure biochemical indicators, and liver samples were extracted for RNA-seq assay. Quantitative real-time PCR (qPCR) was used to further verify the gene expression levels detected by the RNA-seq assay. The EMP group showed significantly decreased blood glucose, triglyceride, cholesterol, non-esterified fatty acid and low-density lipoprotein cholesterol levels, and increased high-density lipoprotein cholesterol levels in serum compared with the type 2 diabetes model (MOD) group. Furthermore, EMP decreased the levels of inflammatory factors IL-1β, IL-6, and IL-8 in the serum compared to the MOD. Liver transcriptome analysis showed EMP affects a large number of upregulated and downregulated genes. Some of these genes are novel and involve in the metal ion binding pathway and the negative regulation of transcription from the RNA polymerase II promoter pathway, which are also closely related to glucolipid metabolism and insulin signaling. Our study provides new knowledge about the mechanism through which SGLT inhibitor can offer beneficial effects in T2D and especially in the hepatic metabolism. These genes found in this study also laid a solid foundation for further research on the new roles and mechanisms of EMP.